2021
DOI: 10.1038/s41398-021-01702-2
|View full text |Cite|
|
Sign up to set email alerts
|

Combining schizophrenia and depression polygenic risk scores improves the genetic prediction of lithium response in bipolar disorder patients

Abstract: Lithium is the gold standard therapy for Bipolar Disorder (BD) but its effectiveness differs widely between individuals. The molecular mechanisms underlying treatment response heterogeneity are not well understood, and personalized treatment in BD remains elusive. Genetic analyses of the lithium treatment response phenotype may generate novel molecular insights into lithium’s therapeutic mechanisms and lead to testable hypotheses to improve BD management and outcomes. We used fixed effect meta-analysis techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Recent studies that leveraged the GWAS dataset from the ConLiGen consortium as well as larger datasets on severe psychiatric disorders from the Psychiatric Genomics Consortium, suggested a high genetic load for schizophrenia (OR for lithium response ranging from 3.46 at the first decile to 2.03 at the ninth decile, compared with the patients in the 10th decile of schizophrenia risk) [66], major depressive disorder (lowest vs highest PRS quartiles OR = 1.54) [67] or attention deficit hyperactivity disorder (β = −0.14; p = 0.01) [68] to be associated with poor lithium response. In addition, a PRS combining variants associated with either schizophrenia or depression was recently shown to be able to improve the prediction of lithium response compared to single disorder PRS (proportion of phenotype variance explained by combined PRS: partial R 2 = 0.91%; schizophrenia-PRS: partial R 2 = 0.82%; depression-PRS partial R 2 = 0.47%) [69]. In the ConLiGen cohort, patients in the highest decile for the combined PRS had 2.5 times higher odds of being poor responders compared with patients in the lowest decile [69].…”
Section: Post-gwas Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies that leveraged the GWAS dataset from the ConLiGen consortium as well as larger datasets on severe psychiatric disorders from the Psychiatric Genomics Consortium, suggested a high genetic load for schizophrenia (OR for lithium response ranging from 3.46 at the first decile to 2.03 at the ninth decile, compared with the patients in the 10th decile of schizophrenia risk) [66], major depressive disorder (lowest vs highest PRS quartiles OR = 1.54) [67] or attention deficit hyperactivity disorder (β = −0.14; p = 0.01) [68] to be associated with poor lithium response. In addition, a PRS combining variants associated with either schizophrenia or depression was recently shown to be able to improve the prediction of lithium response compared to single disorder PRS (proportion of phenotype variance explained by combined PRS: partial R 2 = 0.91%; schizophrenia-PRS: partial R 2 = 0.82%; depression-PRS partial R 2 = 0.47%) [69]. In the ConLiGen cohort, patients in the highest decile for the combined PRS had 2.5 times higher odds of being poor responders compared with patients in the lowest decile [69].…”
Section: Post-gwas Approachesmentioning
confidence: 99%
“…In addition, a PRS combining variants associated with either schizophrenia or depression was recently shown to be able to improve the prediction of lithium response compared to single disorder PRS (proportion of phenotype variance explained by combined PRS: partial R 2 = 0.91%; schizophrenia-PRS: partial R 2 = 0.82%; depression-PRS partial R 2 = 0.47%) [69]. In the ConLiGen cohort, patients in the highest decile for the combined PRS had 2.5 times higher odds of being poor responders compared with patients in the lowest decile [69]. These approaches are based on pleiotropy, i.e., a condition in which the same gene affects multiple phenotypes simultaneously.…”
Section: Post-gwas Approachesmentioning
confidence: 99%
“…Genetic factors are thought to contribute, at least in part, to the large interindividual differences in response to lithium [10][11][12][13][14][15] . So far, only a few genetic studies have identi ed speci c single nucleotide polymorphisms (SNPs) and candidate genes associated with patients' response to lithium or treatmentrelated side effects 10,11,[13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors are thought to contribute, at least in part, to the large interindividual differences in response to lithium [10][11][12][13][14][15] . So far, only a few genetic studies have identi ed speci c single nucleotide polymorphisms (SNPs) and candidate genes associated with patients' response to lithium or treatmentrelated side effects 10,11,[13][14][15][16] . Each employing a genome-wide association study (GWAS) approach, the Taiwan Bipolar Consortium found SNPs in the introns of GADL1 associated with lithium treatment response 17 , whereas the International Consortium on Lithium Genetics (ConLi + Gen) identi ed a locus on chromosome 21 10 , and a follow-up analysis uncovered additional variants within the human leukocyte antigen (HLA) region 14,16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation